Randomised controlled trial of screening for Chlamydia trachomatis to prevent pelvic inflammatory disease: the POPI (prevention of pelvic infection) trial. (8th April 2010) - Oakeshott, Pippa; Kerry, Sally; Aghaizu, Adamma; Atherton, Helen; Hay, Sima; Taylor-Robinson, David; Simms, Ian; Hay, Phillip
Abstract : Objective To determine whether screening and treating women for chlamydial infection reduces the incidence of pelvic inflammatory disease over the subsequent 12 months. Design Randomised controlled trial. Setting Common rooms, lecture theatres, and student bars at universities and further education colleges in London. Participants 2529 sexually active female students, mean age 21 years (range 16-27). Intervention Participants completed a questionnaire and provided self taken vaginal swabs, with follow-up after one year. Samples were randomly allocated to immediate testing and treatment for chlamydial infection, or storage and analysis after a year (deferred screening controls). Main outcome measure Incidence of clinical pelvic inflammatory disease over 12 months. Results Baseline prevalence of chlamydia was 5.4% (68/1254) in screened women and 5.9% (75/1265) in controls. 94% (2377/2529) of women were followed up after 12 months. The incidence of pelvic inflammatory disease was 1.3% (15/1191) in screened women compared with 1.9% (23/1186) in controls (relative risk 0.65, 95% confidence interval 0.34 to 1.22). Seven of 74 control women (9.5%, 95% confidence interval 4.7% to 18.3%) who tested positive for chlamydial infection at baseline developed pelvic inflammatory disease over 12 months compared with one of 63 (1.6%) screened women (relative risk 0.17, 0.03 to 1.01). However, most episodes of pelvic inflammatory disease occurred in women who tested negative for chlamydia at baseline (79%, 30/38). 22% (527/2377) of women reported being tested independently for chlamydia during the trial. Conclusion Although some evidence suggests that screening for chlamydia reduces rates of pelvic inflammatory disease, especially in women with chlamydial infection at baseline, the effectiveness of a single chlamydia test in preventing pelvic inflammatory disease over 12 months may have been overestimated. Trial registration ClinicalTrials.gov NCT00115388 .